(untitled) (Nepalese Journal of Management Research, 2021)
This study aims to identify the relationship between corporate social responsibility and financial performance of commercial banks in Nepal. Out of the 28 commercial banks under the population, only 6 banks were selected as the sample for the study through purposive sampling technique comprising 2 government owned, 2 joint venture and 2 private commercial banks covering financial year ranges from 2016/17 to 2018/2019. The results indicate that CSR exerts positive impact on financial performance of the Nepalese government owned banks and provides great insights for management, to integrate the CSR with strategic intent of the business. In contrary it revealed negative impact on financial performance in joint venture banks. Furthermore CSR have significantly low positive impact on financial performance. The study concluded that the relationship between CSR and firm financial performance differs in every category of Nepalese commercial banks. This study can be used for further research regarding corporate social responsibility and financial performance in cross banking sector as well as cross country comparisons.